Extraction, fractionation and characterization of durian (Durio zibethenius M.) leaf extract as potential source of squalene and its application in gelatin-based film - Kam, Wai Yee (2017)
The utilization of extract from durian leaf by traditional practioners has indicated the presence of phytochemical compounds with anti-inflammatory as well as antioxidant properties. However, there is no updated scientific reports on phytochemical compound recovery from durian leaf via extraction methods. The main objective of this study was to investigate the most efficient extraction method on durian leaf, proceeded by recovery of high squalene content and antioxidant activity via fractionation of the crude leaf extract. Two extraction methods that were applied in this study were ultrasound-assisted extraction (UAE) and accelerated solvent extraction (ASE). The effectiveness of both extraction methods were investigated on the yield of crude leaf extract, DPPH free radical scavenging activity, ferric reducing antioxidant power (FRAP), total phenolic content (TPC), total flavonoid content (TFC) and squalene content. The results revealed that UAE was more efficient than ASE in obtaining natural extract from durian leaf waste with optimum antioxidant activity and squalene content. In addition, UAE was reported to require shorter processing time and less energy required at lower temperature condition. Results from the optimization process revealed that the optimum condition for UAE was 5 min extraction time under continuous mode with the amplitude of 66% (power intensity 261 W/cm2), using 100% hexane at the solvent-sample ratio of 13:1. Under this optimum condition, a crude yield extract of 6.63% was obtained, and possessing antioxidant activity at 6.63 mg/mL TE per 100 mg DW in DPPH assay, 55.96 mg/mL TE per 100 mg DW in FRAP assay, 69.61 g GAE / 100 g DW in TPC and 1210.8 mg QE / 100 mg DW in TFC. Squalene content was reported at 20.56 %. The crude extract sample from UAE’s optimum condition was preceded for further fractionation. The objective was to achieve fractions that were high in antioxidant activity and/or squalene content. Four fractions were obtained from this experiment and labeled as following : ‘A’ contained the highest amount of squalene ( 62.72 mg in 100 mg DW), ‘B’ contained the highest total phenolic content value (18.22 g GAE / 100 g DW), ‘C’ contained the highest DPPH radical scavenging activity (5.82 mg/mL TE / 100 mg DW) and ‘D’ contained highest FRAP value (108.15 mg/mL TE / 100 mg DW) and total flavonoid content (527.27 mg QE / 100 mg DW). This experiment revealed that the non-modified (both physical and chemical) alumina was efficient in the process of recovering squalene from the crude extract. n-hexane was the most efficient eluent for squalene recovery during fractionation. Fractions with high antioxidant activity were efficiently recovered by alumina and silica gel with modification using 10% AgNO3 and 10% NaCl impregnation respectively. Chloroform had efficiently recovered fraction with high antioxidant activity when using non-modified adsorbent material. The four fractions were subsequently incorporated into a gelatin-based packaging film at two usage levels (0.2% and 0.5%). All film samples were tested and compared on physicochemical properties against a negative and a positive control. The present study shows that the incorporation of fraction D from the crude leaf extract was able to enhance the radical scavenging activity in gelatin-based film. Results from the water vapor permeability test revealed that the film samples with added leaf extract fractions were not significantly (p > 0.05) improved compared to the positive control. In addition to the physicochemical tests, the potential use of the film samples were also tested on their final application use as a packaging film for minimally processed durian fruit pulp. All durian fruit pulps wrapped in the gelatin film samples were evaluated on physical changes after storage under refrigerated condition for 4 weeks. The finding of the study revealed that gelatin film with added leaf extracts were not able to control weight loss and color changes of the fruit during storage. Sensory evaluation was carried out by trained panel and the results revealed that the overall acceptance of the durian fruit after storage for three weeks under refrigerated condition were not significantly (p > 0.05) affected by the addition of leaf extract in gelatin film samples. In general, film samples with added leaf extract fractions that were high in antioxidant activity demonstrated improvement in physicochemical properties especially in DPPH radical scavenging activity. Finally, all gelatin film samples with added leaf extract did not bring prominent impact towards the physical changes in durian fruit pulp for the shelf-life extension. This study had revealed that UAE is more appropriate for obtaining a crude extract with maximum antioxidant activity and squalene content from durian leaf waste. Physicochemical properties of gelatin films were significantly improved in antioxidant activity after incorporated with leaf extract. The film samples with added leaf extract also resulted in negligible physical and sensory changes to the durian fruit pulp during storage.